Optimalisasi Pelaksanaan Mediasi di Pengadilan Agama Gorontalo - Sri Wahyuni Husain (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2017)
This study aims to determine the optimization of the implementation of mediation in the Gorontalo Religious Court. This research is a field research with data collection methods in the form of observations, interviews and documentation. Data’s were analyzed using qualitative descriptive. The results of the study found that the implementation of mediation in the Gorontalo Religious Court was not yet fully optimal. Based on the cases decided by the Gorontalo Religious Court in 2016 totaling 1524 and entering the mediation process as many as 87 cases and only 1 case that was successfully mediated (0.1%). Factor failure of the mediation process because the mediation room facilities are still not efficient enough, because the parties to queue, even some mediator judges carry out mediation in the judge's room itself, there is no certified mediator as explained in the Minister of Religion Regulation (PERMA) Number 1 of 2016 about Procedure for Mediation at Court.